2021
DOI: 10.3389/fpsyg.2020.575245
|View full text |Cite
|
Sign up to set email alerts
|

Natural Is Not Always Better: The Varied Effects of a Natural Environment and Exercise on Affect and Cognition

Abstract: The Attention Restoration Theory (ART) has been widely cited to account for beneficial effects of natural environments on affect and attention. However, the effects of environment and exercise are not consistent. In a within-subjects design, participants completed affective and cognitive measures that varied in attentional demands (memory, working memory, and executive function) both before and after exercise in a natural and indoor environment. Contrary to the hypotheses, a natural environment resulted in low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 54 publications
2
27
0
Order By: Relevance
“…We observed mixed results for the short-term memory test since residential green space was found associated with better performance on the first part of the test (Digit Span Forward) requiring moderate attention, whereas no effect was found with the second part of the test requiring greater attention resources (Digit Span Backward). Similar to our findings, an experimental study in 28 persons showed that exercise in a natural environment resulted in the greatest improvement for cognitive tasks that required only moderate attentional demands [ 47 ]. A systematic review with a meta-analysis reported that the natural exposure group performed significantly better than controls on both Digit Span Forward and Digit Span Backward Tests [ 48 ].…”
Section: Discussionsupporting
confidence: 89%
“…We observed mixed results for the short-term memory test since residential green space was found associated with better performance on the first part of the test (Digit Span Forward) requiring moderate attention, whereas no effect was found with the second part of the test requiring greater attention resources (Digit Span Backward). Similar to our findings, an experimental study in 28 persons showed that exercise in a natural environment resulted in the greatest improvement for cognitive tasks that required only moderate attentional demands [ 47 ]. A systematic review with a meta-analysis reported that the natural exposure group performed significantly better than controls on both Digit Span Forward and Digit Span Backward Tests [ 48 ].…”
Section: Discussionsupporting
confidence: 89%
“…Another limitation of our study is that cognitive tasks were performed relatively close to each other, thus making it impossible to rule out a possible learning effect. Numerous studies that have repeatably measured cognition (memory and executive function), throughout the day or during a short period of time, report no learning effect/performance bias [ 38 , 39 , 40 ]. That said, our data indicate that an increased frequency of the test did not yield significantly better accuracy, demonstrating that there was not a substantial learning effect associated with the way this task was administered.…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to boosting people's mental health, city planners may benefit greatly by being aware that people can find a lot to enjoy even in metropolitan areas. Instead of hindering people's emotional, cognitive, and emotional recovery from the stresses of urban life, cities could help facilitate this process [19].…”
Section: Contributions Of Biophilic Designs To Improved Mental Health...mentioning
confidence: 99%